Relationship between Environmental attitude and Frequency of pro environmental behaviour among young adults (International Journal of Food and Nutritional Sciences, 2022)
Environmental degradation is a topic of concern all over the world now. People’s attitude towards environmental protection and restoration influences their overt behavior to make this world a better place to live in. Previous research suggests that the quality of the environment depends on the level of knowledge, attitudes, values, and practices of individuals (Saari et al., 2021). This study is an ex-post facto study that aimed to understand the relationship between environmental attitude and the frequency of pro-environmental behaviour among young adults. Convenience sampling was used to collect the data. The study includes 100 participants of age range 18 to 26 years. Environmental attitude inventory (EAI) 24-items (Milfont & Duckitt, 2010) and frequency of pro environmental behavior 17-items (Whitmarsh & O’Neill, 2010) tools were used to analyse the results. Therefore, understanding the relationship between those can help us plan for increasing the focus of environmental education on construction of attitudes, which in turn would result in pro-social behaviour.